A field study onboard VLCCs for CO2 emission reduction considering EEDI and SEEMP - Tarek A. Ashry; Nasr Abdelrahman Nasr; Nader S. Fahim; Nour A. Marey (Alexandria Engineering Journal)
Recently, the demand for alleviating the environmental impact triggered by shipping industry is continuously on the rise. To meet the aspired expectations in terms of fuel consumption and emission levels, ships have to adhere to and comply with the effective regulations and design recommendations set by Ship Energy Efficiency Management Plan (SEEMP) and Energy Efficiency Design Index (EEDI). The current work seeks to assess the degree and volume of difference made in ship operation after the full implementation of such operational and technical measures both quantitatively and qualitatively. Extensive analysis and measurements are conducted considering 3 phases for a VLCCs. Phases 1 and 2 involved the case of an existing VLCCs prior to and post enforcing SEEMP. Comparably, phase 3 traces the development and installation of innovative energy efficient technologies for a new VLCCs onboard of which both of SEEMP and EEDI are applied. Fuel consumption, CO2 emissions, and EEOI have, respectively, decreased at phase 3 by 82.6 %, 66.8 %, and 71.5 % compared to their counterparts obtained for phase 1. Moreover, ship overall performance for phase 3 has increased by 46.6 % compared to its peers recorded for phase 2. Apparently, SEEMP and EEDI have brought about significant reductions in the accumulation of Greenhouse Gases (GHGs) and provided a real momentum for the efforts towards a greener maritime world.